ANALISIS PENGEMBANGAN MEDIA PEMBELAJARAN E-MODUL PADA MATA PELAJARAN TEKNIK PEMESINAN BUBUT DI SMKS DHUAFA PADANG - Richardo Richardo; Budi Syahri; Purwantono Purwantono; Delima Yanti Sari (Unversitas Negeri Padang, 2024)
The role of education is crucial in individual self-development to overcome faced challenges. The learning process is a fundamental means to enhance this educational role. However, to support an effective learning process, appropriate media is needed to ensure that information received by students is more easily understood. At SMKS Dhuafa Padang, for the lathe machining technique subject, learning media is still limited to whiteboards, textbooks, and PowerPoint presentations, which create student dependency on teachers. The lack of visualization in learning results in students having difficulty understanding the material. Therefore, E-modules become a solution to improve the quality of lathe machining technique learning. E-modules allow students to learn independently with neatly and systematically arranged material, stronger visualization, and interactivity. In conducting this research, the researcher used a Research and Development (R&D) approach and employed the Instructional Development Institute (IDI) development procedure, which has three steps: Define (needs analysis), Develop (e-module media design), and Evaluate (Validity Evaluation). The research instrument used questionnaires filled out by validators (teachers and lecturers), and the research results showed a score of 0.925 for material validity and 0.903 for media validity, indicating that this e-module media is feasible and valid for application as learning media. It is hoped that with the existence of this E-module, it can be utilized as additional learning media in the Lathe Machining Technique learning process.